Strategi Peningkatan Kompetensi Pedagogik: Pelatihan Computational Thinking bagi Calon Guru Matematika - Junaeti, Enjun; Pramitha Muslim, Audra; Ate, Dekriati; Khaedir Lutfi, Muhammad; Sukjaya Kusumah, Yaya; Herman, Tatang (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
The introduction of Computational Thinking (CT) as a crucial skill in the 21st century has now been incorporated into the Merdeka Curriculum in Indonesia. The relatively new concept of CT in Indonesia has led to a lack of complete understanding, with many perceiving it solely as aligned with programming skills or equating it to thinking exactly like a computer. In reality, CT emphasizes an approach to problem-solving. The objective of this initiative is to impart CT-based learning design skills to prospective Mathematics teachers as an integral part of their pedagogical competence. The training is conducted through both synchronous and asynchronous methods. The outcomes encompass the development of CT-based educational media. Evaluation results demonstrate the success of the training in enhancing the capabilities of prospective teachers to apply CT in Mathematics education, particularly concerning topics such as series and fractions.